PROSES METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN KEIRSEY - Intan Fathimah Ahmadah; Rooselyna Ekawati (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2021)
Metacognition plays an important role in problem-solving activities. It will help students to find what the problem is and understand how to get the solution. This study aimed at describing the student's metacognition process based on Keirsey's personality types. This research used qualitative method with descriptive approach and it was conducted involving eight students who have equal mathematical abilities and the same gender. The selected students represented Keirsey’s personality types. They were carried out through two types of tests, namely the Keirsey Temperament Sorter and the Mathematics Ability Test. The result showed that each personality type could through indicators of the metacognition process. However, there are some indicator components missed. Rational and idealist student have not been able to carry out the metacognition process in the regulation stage properly. Guardian and artisan student have been able to carry out the metacognition process well. This study suggests the teacher can facilitate students in each personality type by determining the appropriate learning model, learning activities, and assessments to obtain better results.